P-P44 Clinical outcomes of consecutive patients undergoing distal pancreatectomy over the last decade at a high volume tertiary pancreatic surgery unit. (16th December 2021) - Patel, Bhavik; Fristedt, Richard; Hamady, Zaed; Takhar, Arjun; Armstrong, Tom; Hilal, Mohammad Abu; Karavias, Dimitrios; Arshad, Ali
Abstract: Background: Distal pancreatectomy (DP) enables resection of lesions in the body and tail of the pancreas.  Over the past decade, the Laparoscopic approach has become frequently employed.  There remains scarce outcome data available following laparoscopic distal pancreatectomy over a long time period from high volume centres. Postoperative pancreatic fistula (POPF) remains the main source of morbidity and mortality after DP. The causes of POPF are multifactorial and poorly understood.  The optimal method of pancreatic stump closure is still debated with variation in clinical practice. Methods: All patients that underwent distal pancreatectomy at a UK tertiary pancreatic surgery centre between January 2011 and January 2021 were identified and clinical outcomes examined. Patients undergoing completion pancreatectomies were excluded. Clinical, pathological and surgical data for the included patients was retrospectively collected from the electronic patient record.  Clinically significant POPF was defined as Grade B or C as per the ISGPF guidelines. For stapled stump closure, the Compression Index (CI) was calculated using closed staple height (mm) divided by the pancreatic thickness (mm). High and low CI was defined around the median. Results: 233 patients (n = 90 open and n = 143 laparoscopic) were included in the final analysis. The laparoscopic approach was associated with comparable morbidity and significantly lower blood loss, shorter operative time and shorter length of stay. There were no significant differences in age, sex, final histology, closure technique, or ASA Score of 3 or more amongst patients with clinically relevant POPF (CR-POPF). The POPF group had a significantly higher BMI, drain duration and readmission rate. CI data was available for 78 cases (range 0.04-0.21). There was no significant difference in low vs high CI for patients with CR-POPF. Conclusions: Laparoscopic distal pancreatectomy is associated with favourable clinical outcomes in this series. Stapled vs sutured closure of the pancreatic stump offered equivocal outcomes with relation to POPF. POPF continues to have a significant impact on a clinical recovery as evident from longer drain duration and high readmission rates. Further research is required to try to establish methods for reducing the incidence of POPF after distal pancreatectomy.